ASET SEBAGAI SUBJEK HUKUM DALAM UPAYA PENGEMBALIAN KERUGIAN KEUANGAN NEGARA PADA TINDAK PIDANA KORUPSI - Achmad Rilyadi Sholeh; Setiawan Noerdajasakti (CV. AFDIFAL MAJU BERKAH, 2024)
Corruption is a problem that results in high financial and economic losses in Indonesia. UNCAC has launched recommendations for countries to make arrangements regarding Non-Conviction Based asset Forfeiture (NCB) since 2003 which aims to recover maximum state financial losses. This is based on the fact that the state losses recovered are not proportional to the state financial losses incurred due to corruption crimes. The research used is normative juridical with a statutory approach, conceptual approach, and comparison with other countries. The conception of assets as legal subjects in the NCB is based on the theory of legal fiction where assets in their position as legal subjects make them seem